KAJIAN EPISTEMOLOGIS ILMU UṢŪL AL-FIQH Studi terhadap Pemikiran Abū Isḥāq Ibrāhīm al-Shīrazī al-Fayrūz Abādī - Amir Tajrid (Al-Ahkam, 2012)
This article intends to conduct epistemological critique of the the Book “al-Luma” that  written by Abū Ibrāhīm al-Shīrazī Isḥāq al-Fayrūz Abādī (al-Shīrazī). This paper, trying to explore and criticize the characteristics and knowledge of uṣūl al-fiqh that contained in. There are some important notes: first the thinking of al-Shīrazī on uṣūl al-fiqh is written in the golden era of uṣūl al-fiqh works, that makes the methods and subjects of thought of al-Shīrazī on uṣūl al-fiqh became inspiration for the next generation. Study of content of uṣūl al-fiqh is based on the its method of predecessor leaders. This is proved by the dominance of the comparative method which is used when explores uṣūl al-fiqh of several different leaders view. Second, al-Shīrazī included as experts of uṣūl, which has original thinking and independent. A sharp criticism launched, invite the parties to be impartial towards certain schools of thought. Therefore the presentation of ideas al-Shīrazī on uṣūl al-fiqh is in the sense of kalāmī, because the arguments are built from elements of kalām and prioritize the logic as a tool in assessing and measuring the truth  of uṣūl al-fiqh. Third, al-Luma has fulfilled the basics of science both in ontology, epistemology, and axiology.***Artikel ini bermaksud melakukan kritik epistemologis terhadap Kitab al-Luma’ yang ditulis oleh Abū Isḥāq Ibrāhīm al-Shīrazī al-Fayrūz Abādī (al-Shīrazī). Tulisan ini, secara deskriptif berusaha menggali dan mengkritisi karakteristik dan pengetahuan mengenai ilmu uṣūl al-fiqh yang terkandung di dalamnya. Beberapa catatan penting terhadap kitab ini adalah: pertama, pemikiran uṣūl al-fiqh al-Shīrazī dalam Kitab al-Luma’ ditulis pada era keemasan karya-karya uṣūl al-fiqh, sehingga metode dan pokok-pokok pemikiran uṣūl al-fiqh al-Shīrazī menjadi inspirator generasi berikutnya. Kajian materi uṣūl al-fiqh didasarkan pada metode para tokoh pendahulunya, terbukti pada dominasi metode komparatif yang digunakan ketika mengetengahkan materi uṣūl al-fiqh dari beberapa tokoh uṣūl al-fiqh yang berbeda pandangan. Kedua, al-Shīrazī termasuk dalam barisan ahli ushul mutakallimin yang mempunyai pemikiran orisinil dan merdeka. Kritik tajam yang dilancarkan mengajak para pihak untuk tidak condong terhadap mazhab fikih tertentu. Oleh karena itu penyajian pemikiran uṣūl al-fiqh al-Shīrazī dalam al-Luma’ lebih bersifat kalamī, karena bangunan argumentasi yang melibatkan unsur-unsur kalam dan mengedepankan logika menjadi alat dalam menilai dan mengukur kebenaran ilmu uṣūl al-fiqh. Ketiga, al-Luma’ telah memenuhi dasar-dasar ilmu pengetahuan baik secara ontologi, epistemologi, maupun aksiologi.***Keywords: uṣūl al-fiqh, al-Luma’, epistemologi, al-Shīrazī